Temporary abdominal closure with zipper-mesh device for management of intra-abdominal sepsis - Utiyama,Edivaldo Massazo (2015)
OBJECTIVE: to present our experience with scheduled reoperations in 15 patients with intra-abdominal sepsis. METHODS: we have applied a more effective technique consisting of temporary abdominal closure with a nylon mesh sheet containing a zipper. We performed reoperations in the operating room under general anesthesia at an average interval of 84 hours. The revision consisted of debridement of necrotic material and vigorous lavage of the involved peritoneal area. The mean age of patients was 38.7 years (range, 15 to 72 years); 11 patients were male, and four were female. RESULTS: forty percent of infections were due to necrotizing pancreatitis. Sixty percent were due to perforation of the intestinal viscus secondary to inflammation, vascular occlusion or trauma. We performed a total of 48 reoperations, an average of 3.2 surgeries per patient. The mesh-zipper device was left in place for an average of 13 days. An intestinal ostomy was present adjacent to the zipper in four patients and did not present a problem for patient management. Mortality was 26.6%. No fistulas resulted from this technique. When intra-abdominal disease was under control, the mesh-zipper device was removed, and the fascia was closed in all patients. In three patients, the wound was closed primarily, and in 12 it was allowed to close by secondary intent. Two patients developed hernia; one was incisional and one was in the drain incision. CONCLUSION: the planned reoperation for manual lavage and debridement of the abdomen through a nylon mesh-zipper combination was rapid, simple, and well-tolerated. It permitted effective management of severe septic peritonitis, easy wound care and primary closure of the abdominal wall.